Socialists, communists and post war democracy (an interview with Jose Pedro Renzi) - Candido, Antonio (FCL-UNESP Laboratório Editorial, 2007)
Antonio Candido talks about the Brazilian democratization process in the post war period. He gives his own opinion about the period, analyzing and explaining the leftists (socialists or communists) conceptions and acts, that is, their role in the political life of the country.